Understanding the Origins of Nucleophilic Hydride Reactivity of a Sodium Hydride–Iodide Composite. Issue 21 (1st April 2016) - Hong, Zonghan; Ong, Derek Yiren; Muduli, Subas Kumar; Too, Pei Chui; Chan, Guo Hao; Tnay, Ya Lin; Chiba, Shunsuke; Nishiyama, Yusuke; Hirao, Hajime; Soo, Han Sen
Abstract: Sodium hydride (NaH) has been commonly used as a Brønsted base in chemical syntheses, while it has rarely been employed to add hydride (H − ) to unsaturated electrophiles. We previously developed a procedure to activate NaH through the addition of a soluble iodide source and found that the new NaH–NaI composite can effect even stereoselective nucleophilic hydride reductions of nitriles, imines, and carbonyl compounds. In this work, we report that mixing NaH with NaI or LiI in tetrahydrofuran (THF) as a solvent provides a new inorganic composite, which consists of NaI interspersed with activated NaH, as revealed by powder X‐ray diffraction, and both solid‐state NMR and X‐ray photoelectron spectroscopies. DFT calculations imply that this remarkably simple inorganic composite, which is comprised of NaH and NaI, gains nucleophilic hydridic character similar to covalent hydrides, resulting in unprecedented and unique hydride donor chemical reactivity. Abstract : From one to another : A remarkably simple protocol was applied to activate NaH with soluble iodide ions to effect nucleophilic hydride reactivity with polar π‐electrophiles. The properties of this activated NaH–NaI composite material were elucidated thoroughly with the use of powder X‐ray diffraction, X‐ray photoelectron spectroscopy, solid‐state NMR spectroscopy, and DFT calculations to explain the unusual reactivity of this reinvented NaH material.